The effect of Phyllanthus niruri L extracts on human leukemic cell proliferation and apoptosis induction - Nanda Ayu Puspita; Hasen Alhebshi (Indonesian Journal of Pharmacy, 2019)
Objective: To investigate the effect of Phyllanthus niruri Linn (Euphorbiaceae) in the proliferation of human leukemic cells (MOLT-4 and K562).Methods: Phyllanthus niruri L (P.niruri) was macerated by using various solvents to obtain the crude extracts. Cytotoxicity of the extracts against MOLT-4 and K562 cells was tested using MTT assay to find the IC50 value. To analyse cell cycle progression, cellular DNA was measured using propidium iodide (PI) staining. Apoptosis induction was evaluated using Annexin V-FITC and PI staining and analysed using FACSVerse flow cytometry. Finally, the expression of p53 on MOLT-4 and K562 cell lysate was measured by western blotting, to identify the possible mode of action of the anticancer activity.Results: P. niruri crude extracts demonstrated a potential anti-cancer effect towards MOLT-4 cells (IC50 range was 42.21 ± 4.98 to 97.06 ± 18.29 µg/ml). However, against K562 cells, P.niruri extracts exhibited a lower inhibitory potency (the IC50 was 120.19 ± 8.48 to 256.55 ± 26.22 µg/ml). The results showed the selectivity of the toxic effect of the extracts against MOLT-4 and K562.  To evaluate the possible mechanism of action the anticancer effect, we evaluated P. niruri extract action in apoptosis induction and p53 expression. The results showed that methanol and hexane extract inhibited MOLT-4 cell progression from G1 to S-phase, indicating G1 cell arrest. Moreover, apoptotic cell population following treatment of MOLT-4 and K562 cells with methanol extract was markedly increased, showing morphological signs of apoptosis including membrane degradation and chromatin condensation. Furthermore, we found that there was an increase in p53 expression following MOLT-4 treatment with methanol extract, suggesting that p53 induction may be involved in cell apoptosis.Conclusions: The results indicated the involvement of p53 pathway in the mechanism of anti-cancer activity exerted by P. niruri extract on MOLT-4 cells. However, for cancer cells lacking P53 expression, such as K562 cells, apoptosis might take place via other pathways.